THE IMPACT OF THE COVID-19 PANDEMIC ON THE ECONOMIC ACTIVITY OF THE REPUBLIC OF NORTHERN MACEDONIA: The effects of the crisis on the economy of the Republic of Northern Macedonia - Mustafi, Mahije; Karemani, Sulbije Memeti (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
COVID-19 not only endangers human health but also hits hard on the economy. Isolation and paralysis of public life hits the economies of every country. Before analyzing the links between COVID-19 and the possible economic crisis, we can say that the crises in capitalism are inherent and the virus should be seen as a spark which accelerates the turbines that shake the system. However, while insufficient to predict the extent of the damage that COVID-19 could do to the economy, this starting point is sufficient to anticipate the chain effects. The immediate effect of all these restrictions is the decline in economic activity, which results in declining production and rising prices. We can say that there is a direct cause-and-effect correlation between the virus and the crisis. The economy of the Republic of Northern Macedonia has been hit hard by the Covid 19. pandemic. These six months have paralyzed almost all sectors of the economy in the country. Government aid packages were more social while those for business still remain unused. Companies in northern Macedonia have already been severely affected. The closure of many businesses is accompanied by the dismissal of many workers, which is also associated with a social crisis.Growth in the country for 2020 is projected to be between -1.4 and -3.2 percent - which provides a baseline and unfavorable scenario due to the high uncertainty brought about by the pandemic. In Northern Macedonia, improving governance and strengthening institutions are long-term policies that can address the main causes of continued emigration, in order to maintain a skilled workforce. This can be achieved by accelerating job creation, promoting the private sector, investing in higher education and increasing opportunities for women in the economy. The capital of the diaspora influences the maintenance of social stability and the reduction of poverty in Macedonia and in the future the state should take it more seriously the investments of the diaspora. Weak administrative capacity can cancel the implementation of reforms as well as large critical projects implemented with state guarantees. Political instability and insufficient reform progress could reduce investor confidence. Northern Macedonia’s accession to NATO and the official invitation of the EU Council to open negotiations for EU membership should help accelerate the recovery.